The complete works. - Byron, George Gordon Byron, Baron, 1788-1824 (Byron, George Gordon Byron, Baron, 1788-1824. Works., 2009)
Lord Byron remains, as he was to many of his contemporaries, the defining personality of his age and time, the quintessential late-Romantic: one whose life matched the freedom of imagination and possibility of his poetry, charismatic, irresistible, shocking and, of course, dying young. The full range of his work, however, reveals a less straightforward and less stereotypical writer than this: a thinker as well as a feeler, a poet rather than merely a sensationalist, someone who justifies his ...